"What is the News About Journalism?" An Interview with Arnold S. de Beer. Issue 2 (3rd April 2021) - Wasserman, Herman
Abstract: This article is in the form of an interview between the Founding Editor of Ecquid Novi: African Journaism Studies, Professor Arnold S. de Beer, and his successor and current Editor-in-Chief, Professor Herman Wasserman. The interview covers the founding of the journal, its development and its current standing in the field, as well as highlights of De Beer's long involvement with the journal.